GUILD PAKAN SPESIES BURUNG DI EKOSISTEM SAVANA TAMAN NASIONAL WAY KAMBAS - Ramadhani Ramadhani; Agus Setiawan; Dian Iswandaru; Yulia Rahma Fitriana (JURNAL HUTAN LESTARI, 2023)
The savanna ecosystem in the Elephant Training Center of Way Kamba National Park has the potential as of habitat the birds. The purpose of this study was to analyze and classify bird species based on the type of feed group or guild. Through the method of counting bird data points are taken and recorded. There are 30 species of birds found in the savanna ecosystem which are divided into six types of guilds with the proportions of insectivores 40%, omnivores 33%, granivores 17%, carnivores 4%, nectarivores 3%, and frugivores 3%. The types of bird guild that dominates the savanna ecosystem is insectivorous (insectivores).Keywords: bird, feeding guild, savannaAbstrakEkosistem savana yang ada di Pusat Latihan Gajah Taman Nasional Way Kambas berpotensi untuk menjadi habitat burung. Tujuan penelitian ini adalah untuk menganalisis dan mengklasifikasikan jenis burung berdasarkan jenis kelompok pakan atau guild. Melalui metode point count data burung diambil dan dicatat. Terdapat 30 spesies burung yang terdapat di ekosistem savana yang terbagi menjadi enam jenis guild dengan persentasenya antara lain insectivore 40%, omnivore 33%, granivoree 17%, carnivore 4%, nectarivore 3%, dan frugivor 3%. Tipe guild burung yang mendominasi ekosistem savana adalah pemakan serangga (insectivore).Kata kunci: burung, pakan, savana